Synthesis of Al-doped NaNbO3 rods with enhanced photocatalytic activity - Fernandes, Daiane; Raubach, Cristiane W.; da S. Dias, Vagner; Carvalho, Ramon D.; Moreira, Mario L.; Jardim, Pedro L.G.; Ferrer, Mateus M.; Moreira, Eduardo C.; Frederico de O. Graeff, Carlos [UNESP]; Longo, Elson; da S. Cava, Sergio (Elsevier, 2025)
In this paper, we synthesized NaNbO3 rods with Al(III) (0.00, 0.05 and 0.1 mmol) by the microwave-assisted hydrothermal method and evaluated the influence of doping on photocatalytic activity. The diffractograms reveal the coexistence of two orthorhombic space groups (P21ma and Pbma) for all samples, with the fraction of each varying with the doping concentration. The micrographs show that pure NaNbO3 exhibits a rod-like shape (diameter of ∼200 nm and a length on the order of tens of micrometers). Doping did not induce significant morphological changes; however, the appearance of some cubic grains of varying sizes was observed. The bandgap of the doped samples (3.23 eV) was reduced compared to the pure sample (3.32 eV). The doped samples exhibited superior photocatalytic activity, as evidenced by the removal of the dye Rhodamine B (RhB). The sample containing 0.1 mmol of the impurity ion showed the best photocatalytic discoloration result, achieving 100 % RhB removal in 45 min. The reduced bandgap, greater ability to absorb light, and the lower electron-hole recombination rate (as revealed by photoluminescence emission) contributed to the enhanced photocatalytic performance of the doped samples. Therefore, this study provides a new a reference for future investigations into NaNbO3 doping for photocatalytic applications.
Keywords: Al-doping; Photocatalysis; Rods; Sodium niobate